2016
DOI: 10.1002/slct.201600292
|View full text |Cite
|
Sign up to set email alerts
|

N‐Iodosuccinimide Catalyzed Oxidative Selenocyanation and Thiocyanation of Electron Rich Arenes

Abstract: Selenocyanation and thiocyanation of electron rich arenes have been achieved using N‐iodosuccinimide (NIS) as a catalyst and aq. tert‐butyl hydroperoxide (TBHP) as an oxidant at room temperature. This method works efficiently for indoles, anilines, phenols, and other electron‐rich arene systems to furnish the products in good to excellent yields and exhibits a good regioselectivity. The products synthesized are further used to prepare their corresponding trifluoromethyl derivatives using reported reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 72 publications
(18 reference statements)
0
22
0
Order By: Relevance
“…The group of Langlois also demonstrated that selenocyanate reacted with the Ruppert–Prakash reagent in the presence of a catalytic amount of TBAF to yield the desired trifluoromethylselonelated compounds in moderate to very good yields (Scheme ). The same conditions have been extended to indole derivatives by the group of Prabhu …”
Section: Indirect Se−cf3 Bond Formationmentioning
confidence: 98%
See 1 more Smart Citation
“…The group of Langlois also demonstrated that selenocyanate reacted with the Ruppert–Prakash reagent in the presence of a catalytic amount of TBAF to yield the desired trifluoromethylselonelated compounds in moderate to very good yields (Scheme ). The same conditions have been extended to indole derivatives by the group of Prabhu …”
Section: Indirect Se−cf3 Bond Formationmentioning
confidence: 98%
“…The same conditions have been extended to indole derivativesb ythe group of Prabhu. [49] Inspired by the work reported by Langlois, Rozen and Potash [50] demonstrated the in situ generation of CuCF 3 by reacting fluoroform with copper(I) chloride and potassium tertbutoxide. The thus-formed CuCF 3 reactedw ith selenocyanates to furnish the desired products in very good to excellent yields (Scheme 34).…”
Section: Indirect Seàcf 3 Bond Formationmentioning
confidence: 99%
“…Aryl thio-and selenocyanates are versatile intermediates for various sulfur-and selenium-containing compounds that are of synthetic and biological interest [14][15][16][17][18][19][20][21][22][23][24][25][26]. Aryl thiocyanates are widely employed as building blocks in the synthesis of diverse sulfides [27,28], thiocarbamates [29], thionitriles [30], sulfonic acids [31], sulfonyl chlorides [32], thioesters [33], and sulfonyl cyanides [31] and mainly in the synthesis and functionalization of heterocyclic compounds [25,26,[34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the aforementioned chemical versatility and biological activity, functional organic compounds bearing the thiocyanato and selenocyanate derivatives are highly sought after, and over the years a number of strategies and reagents have been utilized to enable the direct introduction of SCN and SeCN moieties into organic motifs. In particular, direct oxidative thiocyanation of C-H bonds have been achieved by using thiocyanate salts in the presence of oxidizing agents such as Mn(OAc) 3 [15], NCS [47], CAN [48], hypervalent iodine reagents [49], DDQ [50], oxone [51], oxygen [52], DEAD [53], and TBHP [22]. In comparison, direct selenocyanation approaches have not been reported under similar oxidative conditions [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Reported procedures, applied to enriched arenes, utilise this reagent as an electrophilic source with N-iodosuccinimide as a catalyst and tert-butyl hydroperoxide as an oxidant, 8 11 In addition to KSeCN, these methods require the use of blue LEDs and tedious column chromatography.…”
mentioning
confidence: 99%